A collection of children’s game songs for use in teaching of recorder to beginners - Sibindi, Dumezweni (Midlands State University, 2019)
The main purpose of this research was to identify and collect children’s game songs that can be used to teach recorder to beginner students in primary schools of Zimbabwe. The research topic was necessitated by the advocacy of African pianism by professor Akin Euba of Nigeria. African pianism is a concept of using African oriented rhythms to teach the piano in an African way. The researcher saw a gap in using African play songs (in the context of Zimbabwean play songs) to teach the recorder and sought to fill it. This was a qualitative research which prompted the researcher to use a survey approach. The focal point of departure into the research was the three research questions which the researcher formulated. Questionnaires and group interviews were used to collect the data which was then synthesized and transcribed for analysis. Data was divided into three cumulative groups from simple play songs to complex play songs for beginners. The findings of the study revealed that recorder music used in schools is western based and does not have an African appeal to the students. The music books used to teach recorder to beginners have western repertoires. Teachers were trained to teach the recorder using western based approaches and any deviation is seen as breaking away from the norm. It is the researcher’s recommendation that the teaching and learning of recorder be made compulsory in primary schools in Zimbabwe and that children’s game songs be used as a starting point in order to foster learning from known to unknown.